Analisis Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan - Serly Tiva Pratiwi; Rihhadatul Aisya; Hidayatul Aminah; Andry Novrianto (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to analyze the influence of the work environment on employee performance at XYZ company. A conducive work environment is believed to increase employee motivation and productivity, while a less supportive environment can reduce their performance. In this study, the variables tested include physical aspects (workspace, facilities, and cleanliness), social (relationship between employees, supervisor support), and psychological (job satisfaction, work stress). The method used is a quantitative approach with a survey technique using a questionnaire to 100 employees in the company. The data obtained was analyzed using linear regression to find out how much influence each work environment factor had on employee performance. Research results show that the physical, social, and psychological work environment has a significant influence on employee performance. This finding provides recommendations for companies to improve these aspects in order to increase the effectiveness and efficiency of employee work.